Two-dimensional Sequence Homogeneity Testing Against Mixture Alternative - Safaryan, Irina A.; Haroutunian, Evgueni A.; Manasyan, Arsen V. (Mathematical Problems of Computer Science, 2024)
The behavior of linear rank statistics is investigated on models in which various subsequences of observations follow different statistical distributions. Such data can be interpreted both as models of a finite number distribution mixtures and as dependence models. We apply data set simulation to obtain estimates of average and variance of used rank statistics. The modeled and asymptotic results are enough close.